Travailler dans la grande distribution La journée de travail va-t-elle redevenir une question sociale? - Cianferoni, Nicola (Seismo, 2019)
What does it mean to work in the retail sector today? In Switzerland, two giants share almost the whole market. In order to stay competitive, they intensify the work, demand more availability from their employees and deskill certain positions. How do the store managers achieve profitability objectives despite the constraints in this context? How do the cashiers cope with the increasing automation of their jobs? How do the shelf workers reconcile customer contact with ever-increasing time constraints? This book explains how neoliberal working time patterns are taking place in the supermarkets and questions the evolution of the working day in our society. The study is based on 78 interviews with managers, shop floor workers and union officers. Nicola Cianferoni is a post-doctoral researcher at the University of Geneva and the University of Neuchâtel in Switzerland.